Influence of rapid COVID-19 vaccine development on vaccine hesitancy - Rosenthal, Sonny (2022)
In the race to deploy vaccines to prevent COVID-19, there is a need to understand factors influencing vaccine hesitancy. Secondary risk theory is a useful framework to explain this, accounting for concerns about vaccine efficacy and safety.